Invisible. - Quinz, Emanuele; Buci-Glucksmann, Christine; Marchetti, Luca; Pierini, Marco; Palazzo delle Papesse Centro Arte Contemporanea, Siena (Prato-Siena : Palazzo delle Papesse Centro Arte Contemporanea, 2004)
Boissier, Jean-Louis ; Eliasson, Olafur ; Hansen, Heiko ; Evans, Helen ; Maebayashi, Akitsugu ; Mendoza, Cristobal ; Novak, Marcos ; Rokeby, David ; Schmitt, Antoine ; Shaw, Jeffrey
Palazzo delle Papesse, Siena, 9 ottobre 2004 - 9 gennaio 2005
kunstcatalogus